THE DIRECTION OF THE SPORTS INDUSTRY ACCORDING TO THE 7th NATIONAL SPORTS DEVELOPMENT PLAN (2023-2027) - Noriya, Wanchalee (Journal of Modern Sport Management, 2022)
In this article, the author aims to study the fifth issue of the direction of the sports industry according to the 7th National Sports Development Plan (2023-2027). The issue is promoting and supporting the development of the sports industry. The issue was studied by analyzing and synthesizing related documents. Thai sports industry can be transformed by creating added value through stakeholders at all levels. They must consider the changing direction of the world sports industry to develop the competitiveness of sports-related industry businesses so that it covers the manufacturing sector, trade sector, and sports service sector. They must also support national and international sports events, support the organization of the private sector’s sports events, and constantly promote local identity sports tourism culture. This concrete approach ensures that the direction of the Thai sports industry will achieve its vision and goals. To achieve the 7th National Sports Development Plan (2023-2027), stakeholders at the policy level, industry drive level, and implementation level must understand the issues in the sports industry, holistic sports management, and the sports industry ecosystem. They must be able to implement all the national sports policies, is strategy-oriented, and implements a continuous monitoring system to ensure the efficiency and effectiveness of set goals.